Pengaruh CAR, ROA, LDR, PPAP, NPM terhadap financial distress pada Bank BPR Kota Semarang - Ansista Cyntya Octavella; Widati, Listyorini Wahyu (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The study's overarching goal is to demonstrate that CAR, ROA, LDR, PPAP, and NPM all contribute to financial stress in some way. The sample for this research consists of all Semarang City BPRs that are currently registered with the Financial Services Authority for the years 2019-2021. The researchers here employ a technique called purposive sampling to choose their sample size of 68 participants. Using multiple linear regression, we examined the hypothesis that ROA and NPM would have an impact on financial distress and found that they do. Meanwhile, the capital adequacy ratio, the loan-to-deposit ratio, and the cushion for possible losses on earning assets have little bearing on financial distress.